Work Psychology / Understanding Human Behavior in the Workplace - Arnold John; Randall Ray (Pearson, 2010)
An accessible and fascinating examination of human behavior in today's workplace. Preface, Acknowledgements, W(Sr(Brk Psychology: An Initial Orientation, Theory and Research and Practice in Work Psychology, Individual Differences, The Foundations of Personnel Selection: Analyzing Jobs and Competencies and Selection Effectiveness, Personnel Selection and Assessment Methods: What Works?, Assessing Performance at Work, Attitudes at Work and the Employment Relationship, Approaches to Work Motivation and Job Design, Design at Work, Communication Technology, Training and Development, Stress and Well-Being at Work, Groups and Teams and Teamwork, Leadership, Careers and Career Management, Understanding Organizational Change and Culture, Glossary of Terms, References, Index.s